Early Host Interactions That Drive the Dysregulated Response in Sepsis - Kerrigan, Steven W.; Devine, Tatyana; Fitzpatrick, Glenn; Thachil, Jecko; Cox, Dermot (Frontiers in Immunology, 2019)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. While many individual cells and systems in the body are involved in driving the excessive and sometimes sustained host response, pathogen engagement with endothelial cells and platelets early in sepsis progression, are believed to be key. Significant progress has been made in establishing key molecular interactions between platelets and pathogens and endothelial cells and pathogens. This review will explore the growing number of compensatory connections between bacteria and viruses with platelets and endothelial cells and how a better understanding of these interactions are informing the field of potential novel ways to treat the dysregulated host response during sepsis.